2011
DOI: 10.1177/194008291100400209
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Composition of Androstachys johnsonii Woodland across Various Strata in Gonarezhou National Park, Southeast Zimbabwe

Abstract: A study on the structure and composition of Androstachys johnsonii Prain (Euphorbiaceae) woodland across three strata was conducted in Gonarezhou National Park (GNP), southeast Zimbabwe. Specifically, the objectives of the study were: (i) to determine the spatial structure and composition of A. johnsonii woodland in GNP and (ii) to determine factors that influence the structure and composition of A. johnsonii woodland in GNP. This study was based on a stratified random design with three major soil groups, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Spirostachys, Dichrostachys and Acacia genera which are known palatable quality browse suitable for black rhino's feed [20] [21] were recorded with high frequency occurrence within the northern side of the Runde River study stratum, suggesting it to be a more suitable sanctuary space for the proposed re-introduction of black rhinos in northern GNP. Earlier studies in GNP confirmed abundance of Spirostachys woodlands [31] and Acacia woodlands [24] within northern GNP. The study results highlighted that north of Runde River Table 2).…”
Section: Discussionmentioning
confidence: 71%
“…Spirostachys, Dichrostachys and Acacia genera which are known palatable quality browse suitable for black rhino's feed [20] [21] were recorded with high frequency occurrence within the northern side of the Runde River study stratum, suggesting it to be a more suitable sanctuary space for the proposed re-introduction of black rhinos in northern GNP. Earlier studies in GNP confirmed abundance of Spirostachys woodlands [31] and Acacia woodlands [24] within northern GNP. The study results highlighted that north of Runde River Table 2).…”
Section: Discussionmentioning
confidence: 71%
“…Gonarezhou has a relatively low relief, with the park altitude varying between 165 m above sea level to 578 m above sea level. The study area was stratified following Gandiwa et al (2011). Gonarezhou was divided into three strata based on natural and physical features.…”
Section: Methodsmentioning
confidence: 99%
“…Baobab damage by elephants was assessed on a 4-point scale, from 0 = no damage, 1 = slight damage with few scars: 2 = moderate damage with numerous scars; 3 = severe damage with the tree scarred deeply and 4 = tree dead or felled (Swanepoel 1993). Moreover, elephant dung counts following Gandiwa et al (2011), grass height, habitat site relief elevation (using a Global Positioning System (GPS) unit) and habitat site rockiness (through visual inspection) in belt transects were recorded. Data were first summarized by descriptive statistics for each belt transect.…”
Section: Methodsmentioning
confidence: 99%
“…Mean annual rainfall at the study site averages 466 mm, and mean monthly maximum temperatures range between 26°C in July and 30°C in January, whereas mean monthly minimum temperatures range between 9°C in June and 24°C in January (Gandiwa et al. ). Granite is located in the east and has higher tree species diversity than basalt in the west.…”
Section: Methodsmentioning
confidence: 99%